2019
DOI: 10.14411/fp.2019.007
|View full text |Cite
|
Sign up to set email alerts
|

Rhipicephalus sanguineus sensu lato from dogs and dromedary camels in Riyadh, Saudi Arabia: low prevalence of vector-borne pathogens in dogs detected using multiplexed tandem PCR panel

Abstract: Despite the global distribution of the brown dog tick, Rhipicephalus sanguineus (Latreille, 1806) sensu lato (s.l.), limited information exists about their identity from the Arabian Peninsula. Ticks from free roaming urban dogs and dromedary camels in Riyadh, Saudi Arabia were morphologically identified, confirmed with scanning electron microscopy and characterised at mitochondrial DNA (cox1, 12S rDNA and 16S rDNA). A total of 186 ticks were collected from 65 free roaming dogs (n = 73) and 84 dromedary camels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 60 publications
0
33
2
Order By: Relevance
“…While R. sanguineus (s.l.) was not found on camels in this study, this tick is known to occur on dogs in Riyadh [61].…”
Section: Discussioncontrasting
confidence: 60%
“…While R. sanguineus (s.l.) was not found on camels in this study, this tick is known to occur on dogs in Riyadh [61].…”
Section: Discussioncontrasting
confidence: 60%
“…sanguineus can develop well under different conditions in terms of temperature (e.g., 20-35°C) and relative humidity (e.g., 35-95%) [47]. In a previous study Chandra et al, (2019) have shown that H. Dromedarii is the most common tick parasitising dogs in Riyadh province.This tick preferentially parasitises camels, although has been known to parasitise other ungulates [48,49]. In this study, we did not collected ticks from dogs and cats from Asir province hence it is difficult to conclude the presence of these parasites in Asir province but not in Riyadh province.…”
Section: Resultsmentioning
confidence: 97%
“…Most of the detected pathogens are vectored by Rhipicephalus sanguineus (s.l), a tick species displaying a worldwide geographical distribution [7,36]. Rh.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations